2012
DOI: 10.1086/668016
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among Healthcare Workers, United States, 1995–2007

Abstract: OBJECTIVE-We examined surveillance data to describe the epidemiology of tuberculosis (TB) among healthcare workers (HCWs) in the United States during the period 1995-2007.DESIGN-Cross-sectional descriptive analysis of existing surveillance data. CONCLUSIONS-Healthcare institutions may benefit from intensifying TB screening of HCWs upon hire, especially persons from countries with a high incidence of TB, and encouraging treatment for latent TB infection among HCWs to prevent progression to TB disease. SETTING A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…As shown in Table 10, we found little consistency in estimates of the occupational burden of TB in HCWs. In five studies, the incidence rate among HCWs was lower than that of the general population (200,202,203,218,219), yielding an estimated burden of zero. Among those with an appreciable burden (IRR > 1), the occupational burden ranged from 0.1% (198) to 8.9% (198).…”
Section: Occupational Burden Of Tb and Capmentioning
confidence: 99%
“…As shown in Table 10, we found little consistency in estimates of the occupational burden of TB in HCWs. In five studies, the incidence rate among HCWs was lower than that of the general population (200,202,203,218,219), yielding an estimated burden of zero. Among those with an appreciable burden (IRR > 1), the occupational burden ranged from 0.1% (198) to 8.9% (198).…”
Section: Occupational Burden Of Tb and Capmentioning
confidence: 99%
“…In a recent meta-analysis, HCWs have been estimated to be both at high risk for active (A) and latent tuberculosis infection (LTBI) based on the results of epidemiological studies conducted in high and intermediate incidence countries [2]. A follow-up study carried out among a large number of North American hospital workers during the period 1995-2007 reported that TB incidence rates among HCWs were similar to those of the general population [6], foreign birth being the major risk factor of LTBI [7][8][9][10][11][12][13]. Moreover, a recent retrospective cohort study found an extremely low rate of Tuberculin Skin Test (TST) conversion among a large population of HCWs working in the low TB-incidence United States.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, debate has opened in the US as to whether IGRAs should be used for repeated testing of HCWs as most annual conversions among HCWs in low TB-incidence settings appear to be false-positives [57,58]. Under that assumption, it has been questioned whether it would be justifiable to subject HCWs to annual testing [59,60], given the parallel observation that annual TST conversion rates are below 1 % in most US hospitals, where strong measures to limit nosocomial TB transmission have been in place [61]. However, the early analysis of Nettleman et al [48], which demonstrated cost effectiveness of annual screening, showed that an assumed annual conversion rate of only 0.4 % implies that 16.8 % of all physicians will become infected with MTB during their professional working lifetime.…”
Section: Discussionmentioning
confidence: 99%